2008
DOI: 10.1111/j.1472-765x.2007.02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fermentation conditions for the expression of sweet-tasting protein brazzein in Lactococcus lactis

Abstract: Aims:  To improve the production of sweet‐tasting protein brazzein in Lactococcus lactis using controlled fermentation conditions. Methods and Results:  The nisin‐controlled expression system was used for brazzein expression. The concentration of nisin for induction and the optical density (OD) at induction were therefore optimized, together with growth conditions (medium composition, pH, aerobic growth in the presence of hemin). Brazzein was assayed with ELISA on Ni‐NTA plates and Western blot. Use of the M‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 12 publications
3
16
1
Order By: Relevance
“…However, glucansucrase activity was more than 30 % less than the controls lacking hemin and 40 % less than previous bioreactor batch cultures. Similar inverse effects of increased cell density with poor product accumulation using the NICE system were previously observed with recombinant GFP (Oddone et al 2007) and brazzein (Berlec et al 2008) optimization studies. These results suggest that reduced protein expression in the presence of heme is not strain or culture condition-dependent and therefore should be avoided.…”
Section: Discussionsupporting
confidence: 73%
“…However, glucansucrase activity was more than 30 % less than the controls lacking hemin and 40 % less than previous bioreactor batch cultures. Similar inverse effects of increased cell density with poor product accumulation using the NICE system were previously observed with recombinant GFP (Oddone et al 2007) and brazzein (Berlec et al 2008) optimization studies. These results suggest that reduced protein expression in the presence of heme is not strain or culture condition-dependent and therefore should be avoided.…”
Section: Discussionsupporting
confidence: 73%
“…However, the quantities of the recombinant mabinlin II proteins were low, as in previous reports of the expression of brazzein expression in L. lactis (Berlec et al 2006). The production of brazzein induced by bacteriocins, could be improved in L. lactis by changing the components of the growth medium, the growth conditions, or the pH of the fermentation environment (Berlec et al 2008;Bogovic-Matijasic et al 2001;Cheigh et al 2002;Li et al 2002a). This suggested that gene expression was favored at pH levels below those optimal for growth.…”
Section: Discussionmentioning
confidence: 79%
“…Quantification and concentration of the recombinant mabinlin II proteins by ELISA HisSorb Ni-NTA plates (Qiagen, Hilden, Germany) were used for immobilization of the recombinant mabinlin II proteins, as previously described (Berlec et al 2008). ELISA was performed for the quantification of the recombinant protein samples, including concentrated total soluble proteins and cultured supernatants, in accordance with the manufacturer's instructions.…”
Section: Recombinant Expression Of Mabinlin II In L Lactismentioning
confidence: 99%
“…Despite these changes, L. lactis has been studied under both anaerobic (Lv et al 2005) and aerobic conditions (Cabo et al 2001;Liu et al 2006). Under aerobic conditions, the addition of exogenous catalase (Duwat et al 1995) or hemin (Berlec et al 2008) was found to improve the survival of L. lactis cells exposed to oxygen. Additionally, aeration conditions for the maximum production of both biomass and bacteriocins-not always coincident events-can differ between species (Vásquez et al 2004).…”
Section: Nisin Maximum Concentrationmentioning
confidence: 97%